Knowledge regarding postexposure prophylaxis of HIV among nurses - Dhital PS; Sharma S; Poudel P; Dhital PR (Dove Medical Press, 2017)
Puja Sharma Dhital,1 Sarojini Sharma,2 Pratik Poudel,3 Pankaj Raj Dhital4 1Adult Health Nursing, Nepal Polytechnic Institute, College of Nursing, 2Adult Health Nursing, BP Koirala Memorial Cancer Hospital, 3Department of Radiology, College of Medical Sciences, Bharatpur, 4Department of Agricultural Extension and Rural Sociology, Agriculture and Forestry University, Rampur, Nepal Abstract: Fifty nurses working in BP Koirala Memorial Cancer Hospital, Bharatpur, were selected by probability simple random sampling technique for determining the knowledge level about postexposure prophylaxis (PEP) of HIV among nurses during 2014. A descriptive design, semistructured self-administered questionnaire was used for the study. The study showed that 48% of respondents had knowledge on the meaning of PEP, only 39.39% respondents were aware of the first aid management getting needle prick injury, 60% were aware of the best time to start PEP of HIV and 56% respondents had knowledge about the time schedule of HIV test after exposure. Although the respondents answered most of the questions correctly, they had knowledge deficit in certain areas. The respondents’ knowledge in this regard needs to be improved with time-to-time awareness program and periodic training, which ultimately helps to decrease the transmission of disease and reduces mortality and morbidity. Keywords: needle prick injury, transmission, PEP, HIV